Exploratory social network analysis with Pajek - Nooy, Wouter de 1962- (Cambridge University Press, 2005)
This was the first textbook on social network analysis integrating theory, applications, and professional software for performing network analysis (Pajek). Step by step, the book introduces the main structural concepts and their applications in social research with exercises to test the understanding. An application section explaining how to perform the network analyses with Pajek software follows each theoretical section. Pajek software and datasets for all examples are freely available, so the reader can learn network analysis by doing it. In addition, each chapter offers case studies for practising network analysis. In the end, the reader has the knowledge, skills, and tools to apply social network analysis in all social sciences, ranging from anthropology and sociology to business administration and history.
Keywords: Pajek (Electronic resource)